PTU-137 A technique for circular stapled cervical anastomosis in three phase minimally-invasive oesophagectomy. (22nd June 2015) - Deutsch, C; Rashid, F; Tan, B; Safranek, P
Abstract : Introduction: Minimally-invasive oesophagectomy (MIO) is an increasingly popular strategy for oesophageal cancer resection in appropriately selected patients. In three-stage procedures, the oesophagus and stomach are mobilised thoracoscopically and laparoscopically, with a mini-laparotomy for conduit formation and specimen removal. The conduit is then delivered into the neck for construction of the oesophagogastric anastomosis. Traditionally the anastomosis is either entirely hand-sewn, or is semi-mechanical. Here, we discuss the use of fully mechanical anastomosis using a circular stapler (CS) in selected patients and report the clinical details, early outcomes. Method: Patients undergoing MIO at our centre from November 2014 were considered for CS anastomosis using a gastrointestinal circular stapler (Ethicon™, UK). The clinical conditions necessary for use of CS were assessed at the time of surgery, the primary criterion being the availability of a sufficiently long conduit. All patients receiving a successful fully mechanical anastomosis are included. Results: Four patients underwent CS anastomosis. Age range was 58–79 and included 2 male and 2 female patients. The first case had an area of proximal Barrett's dysplasia which would have required a high hand sewn anastomosis. Another patient had very significant comorbid factors including rheumatoid arthritis and long-term corticosteroid and methotrexate use. In all of these cases, the anastomosis was successfully formed on first attempt. No early leaks occurred. Conclusion: Use of CS is described for minimally invasive two phase and open oesophagectomy, and is occasionally reported for three-stage MIO. The majority of surgeons use the either fully hand-sewn or partially mechanical techniques for cervical anastomoses. We describe a simple technique for a stapled neck anastomosis which is faster to construct and enables a more proximal oesophageal resection without difficulty. Disclosure of interest: None Declared. References: Price TN, Nichols FC, Harmsen WS, Allen MS, Cassivi SD, Wigle DA, Shen KR, Deschamps C. A comprehensive review of anastomotic technique in 432 esophagectomies. Ann Thorac Surg. 2013;95(4):1154–60 Li J, Shen Y, Tan L, Feng M, Wang H, Xi Y, Leng Y, Wang Q. See comment in PubMed Commons belowCervical triangulating stapled anastomosis: technique and initial experience. J Thorac Dis. 2014;6(3):S350–4